A Legal Analysis of Abortion Medications in Pharmacies and Their Relationship to Criminal Acts of Abortion in Bengkulu Province - Nova Futri Utami; M Rochman; Himawan Ahmed Sanusi (Institute of Advanced Knowledge and Science, 2026)
The phenomenon of abortion in Indonesia is a complex issue because it involves legal, social, and moral aspects. Abortion is generally still viewed as an illegal act, given that the provisions of Law No. 36 of 2009 on Health (later amended by Law No. 17 of 2023) only permit abortion under specific conditions, such as medical emergencies and pregnancies resulting from rape. These restrictions, coupled with social stigma and religious norms, lead some women to seek abortions clandestinely, which can result in psychological impacts and health risks. This study aims to examine the legal framework governing the distribution of abortion medications in pharmacies based on Indonesian legislation, as well as to analyze the relationship between the distribution of such medications and criminal abortion offenses, along with the criminal liability of the parties involved. The research design employed is an empirical legal study using a statutory approach and a socio-legal approach. The results of the study indicate that, from a legal perspective, the distribution of drugs that could potentially be used as abortion drugs has been comprehensively regulated in various laws and regulations, including the Criminal Code (KUHP), the Health Law, and the Minister of Health Regulation on Pharmaceutical Service Standards in Pharmacies. However, implementation has not been optimal due to weak oversight, the widespread circulation of illegal drugs, and low compliance with applicable regulations. Additionally, there is a connection between the circulation of abortion drugs and criminal abortion offenses; although indirect, this connection can facilitate the occurrence of illegal abortions. Criminal liability in this context is multi-subject and may be imposed on pharmacies, sellers of illegal drugs, users, and healthcare workers in accordance with their respective roles and degrees of fault under applicable criminal law provisions.